Investment, Uncertainty, and Irreversibility in Ghana - Pattillo, Catherine A. (International Monetary Fund, 1997)
Panel data on Ghanaian manufacturing firms are used to test predictions from models of irreversible investment under uncertainty. Information on the entrepreneur's subjective probability distribution over future demand for the firm's products is used to construct the expected variance of demand, which is used as a measure of uncertainty. Empirical results support the prediction that firms wait to invest until the marginal revenue product of capital reaches a firm-specific hurdle level. Moreover, higher uncertainty raises the hurdle level that triggers investment, and uncertainty has a negative effect on investment levels that is greater for firms with more irreversible investment